Proses Stimulasi Literasi Anak Prasekolah Oleh Guru - Siwi, Chandarani Paramitha, Dr. Lisnawati Ruhaena, M.Si., Psikolog (2017)
UNESCO showing public interest read Indonesia ranks 60 out of 61 countries in the world that shows the interest of the people of Indonesia in reading and writing is relatively low, therefore, the habit of reading should be introduced to children, but there are pros and cons of introducing reading, writing and arithmetic in children preschool. Literacy is the ability to read and write on a child into one of the literacy skills that are owned by preschool, teacher Kindergarten prepare these skills for children entering further education, because such skills are a requirement in a test Admission (PSB) in schools. This research aims to understand how stimulation done by teachers in enhancing literasi a preschool child , and to know the factors that support as well as a factor that impedes stimulation literasi a preschool child. This study adopted qualitative approaches fenomenologis collected data collected through interviews , observation , and documentation teachers to 4 in kindergarten Aisyiyah 14 Danukusuman , Serengan , Surakarta , 1 among them as principal and more as the guardian class. The result showed that kindergarten teacher Aisyiyah 14 Danukusuman do stimulation literacy for children aged 4 to 6 years, stimulation done by teachers use some props by applying variation literacy method of mimic the method , a method of reading syllables , and method of learning while playing in the form of using a liquid , singing and dancing, of these methods, the method of learning is playing ; playing is learning appropriate and reading syllable method is a method that unappropriate for children. Besides stimulation literacy be done in klasikal and individuals. Stimulation klasikal by making the art projects or introduce props then to reading and writing and singing and dancing around classrooms. Stimulation individuals with personal approach then spell out letters and introduce various the form of the letter by moving the children, make curved lines, movement back and forth or movement to side to side to form a letter, with guidance the individual created the quality of communication interactive was caused by both sides interaction between teachers to students.